Produktivitas Kerja Pada Penjahit Bordir Di Kabupaten Malang - Arifah, Lailatul Nur; Rupiwardani, Irfany; Yohanan, Agus (Jurnal Kesehatan Lingkungan, 2022)
Found factors that affect work productivity such as complaints of fatigue and the physical environment that feels stuffy and lack of lighting. This study aims to determine the factors that affect work productivity on embroidery tailors at CV. Subur Makmur Fern Embroidery Palace, Malang Regency. This study use an analytical research design with a cross sectional approach. The research sample consisted of 15 embroidery tailors. Analysis of research results used ordinal logistic regression test. The result shows that the significant value is 0.045. So it can be concluded that there is an influence on the variables of age, motivation, years of service and lighting on the embroidery tailor at CV. Subur Makmur Fern Embroidery Palace, Malang Regency. For this reason, it is recommended to add artificial light such as lamps at several points in the room, adjust the distance from the table and routine health checks for all workers